1996
DOI: 10.1113/jphysiol.1996.sp021623
|View full text |Cite
|
Sign up to set email alerts
|

Glial potassium channels activated by neuronal firing or intracellular cyclic AMP in Helix.

Abstract: 1. Cell-attached and whole-cell patch clamp experiments were performed on satellite glial cells adhering to the cell body of neurones in situ within the nervous system of the snail Helix pomatia. The underlying neurone was under current-or voltage-clamp control. 2. Neuronal firing induced a delayed (20-30 s) persistent (3-4 min) increase in the opening probability of glial K+ channels. The channels were also activated by perfusing the ganglion with a depolarizing high-K+ saline, except when the underlying neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…6 A3,A4 ). This result is consistent with the facts that K ϩ channels are abundant on astrocytes in the SON (Armstrong et al, 2005), and burst firing can activate membrane K ϩ channels on neighboring astrocytes (Gommerat and Gola, 1996). K ϩ channel activity is closely associated with water transportation.…”
Section: Suckling-evoked Gfap Reexpansion By Transiently Increasing Esupporting
confidence: 79%
“…6 A3,A4 ). This result is consistent with the facts that K ϩ channels are abundant on astrocytes in the SON (Armstrong et al, 2005), and burst firing can activate membrane K ϩ channels on neighboring astrocytes (Gommerat and Gola, 1996). K ϩ channel activity is closely associated with water transportation.…”
Section: Suckling-evoked Gfap Reexpansion By Transiently Increasing Esupporting
confidence: 79%
“…However, when we applied IBMX (100 M) to control for this effect, we observed no change in the extent of EP cell migration (data not shown). Because IBMX and caffeine have generally been found to have similar membrane permeabilities (Kehoe, 1990;Usachev et al, 1995;Gommerat and Gola, 1996), this observation supports our conclusion that the effect of caffeine on EP cell migration resulted from the release of intracellular Ca 2ϩ . causes a concentrationdependent inhibition of migration.…”
Section: Effects Of Calcium Manipulations On Migrationsupporting
confidence: 78%
“…These authors reported that thrombin, which is likely to enter the retina during a breakdown of the blood-brain barrier, inhibited K IR through a rise in intracellular [Ca 2ϩ ]. Gommerat and Gola (1996; Fig. 4) succeeded in demonstrating activation of K IR channels in satellite glial cells in Helix pomatia when the underlying neuron was depolarized.…”
Section: Modulation Of K E Muffling Modulation Of K ؉ Conductancementioning
confidence: 89%
“…The inset diagram of the cells shows the experimental design. (Taken with permission from Gommerat and Gola, 1996). homeostasis requires very little energy, its requirements might be comfortably met by glycolysis alone (Fig.…”
Section: Implications For Glial Cell Energy Metabolismmentioning
confidence: 99%